Carbon sequestration rate, nitrogen use efficiency and rice yield responses to long-term substitution of chemical fertilizer by organic manure in a rice–rice cropping system - Nafiu Garba HAYATU; Yi-ren LIU; Tian-fu HAN; Nano Alemu DABA; Lu ZHANG; Zhe SHEN; Ji-wen LI; Haliru MUAZU; Sobhi Faid LAMLOM; Hui-min ZHANG (Journal of Integrative Agriculture, 2023)
Combined application of chemical fertilizers with organic amendments was recommended as a strategy for improving yield, soil carbon storage, and nutrient use efficiency. However, how the long-term substitution of chemical fertilizer with organic manure affects rice yield, carbon sequestration rate (CSR), and nitrogen use efficiency (NUE) while ensuring environmental safety remains unclear. This study assessed the long-term effect of substituting chemical fertilizer with organic manure on rice yield, CSR, and NUE. It also determined the optimum substitution ratio in the acidic soil of southern China. The treatments were: (i) NPK0, unfertilized control; (ii) NPK1, 100% chemical nitrogen, phosphorus, and potassium fertilizer; (iii) NPKM1, 70% chemical NPK fertilizer and 30% organic manure; (iv) NPKM2, 50% chemical NPK fertilizer and 50% organic manure; and (v) NPKM3, 30% chemical NPK fertilizer and 70% organic manure. Milk vetch and pig manure were sources of manure for early and late rice seasons, respectively. The result showed that SOC content was higher in NPKM1, NPKM2, and NPKM3 treatments than in NPK0 and NPK1 treatments. The carbon sequestration rate increased by 140, 160, and 280% under NPKM1, NPKM2, and NPKM3 treatments, respectively, compared to NPK1 treatment. Grain yield was 86.1, 93.1, 93.6, and 96.5% higher under NPK1, NPKM1, NPKM2, and NPKM3 treatments, respectively, compared to NPK0 treatment. The NUE in NPKM1, NPKM2, and NPKM3 treatments was higher as compared to NPK1 treatment for both rice seasons. Redundancy analysis revealed close positive relationships of CSR with C input, total N, soil C:N ratio, catalase, and humic acids, whereas NUE was closely related to grain yield, grain N content, and phenol oxidase. Furthermore, CSR and NUE negatively correlated with humin acid and soil C:P and N:P ratios. The technique for order of preference by similarity to ideal solution (TOPSIS) showed that NPKM3 treatment was the optimum strategy for improving CSR and NUE. Therefore, substituting 70% of chemical fertilizer with organic manure could be the best management option for increasing CSR and NUE in the paddy fields of southern China.